COMPARATIVE ANALYSIS OF THE TECHNICAL PERFORMANCE OF YOUNG VOLLEYBALL PLAYERS - Rahimov Shermat Mirzarahimovich (Galaxy International Interdisciplinary Research Journal, 2023)
Based on the statistical analysis of test results, the article examines the technical training of volleyball players of four training groups in the first year of study at the Youth Sports School. Differences in some aspects of the technical training of the studied groups were identified. Results of statistical analysis are presented.